APLIKASI PERPINDAHAN KALOR PADA SETRIKA UAP - Fatiatun, Fatiatun; Fajeri, Mei Laelatul; Ni’mah, Azizatun; Faizin, Faizin (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2022)
The use of electric irons can be used anywhere as long as there is an electrical installation. Electric irons lead to waste of electricity. In contrast to the use of a steam iron, it is a special choice when you need to iron a large number of clothes. A steam iron is an iron that can release steam from its base. The hot steam of the iron can help remove bad odors from clothes. When a steam iron is used for ironing clothes, heat transfer will occur. Heat transfer occurs because of the temperature difference in the material.